Os novos desafios à proteção de dados pessoais no início do século XXI - Costa, Graça Maria Neves Pacheco (2017)
Data protection is a fundamental right which faces new challenges at the beginning of the XXI century. The problems raised by these challenges are particularly potentiated by technological developments. Profiling, ambient intelligence and single out are highlighted by this subject. The solutions must focus on prevention, the right to be forgotten, privacy enhancing technologies, transparency and on data subjects’ awareness and empowerment.